Biochemistry. - Berg, Jeremy Mark, 1958-; Stryer, Lubert, 1938-; Tymoczko, John L., 1948- (New York : Freeman, 2007)
In the new edition of Biochemistry, instructors will see the all the hallmark features that made this a consistent bestseller for the undergraduate biochemistry course: exceptional clarity and concision, a more biological focus, cutting-edge content, and an elegant, uncluttered design. Accomplished in both the classroom and the laboratory, coauthors Jeremy Berg and John Tymoczko draw on the field's dynamic research to illustrate its fundamental ideas.
Keywords: Biochemie